1995
DOI: 10.1029/94rg03020
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional seismic models of the Earth's mantle

Abstract: Accurate models of the distribution of elastic heterogeneity in the Earth's mantle are important in many areas of geophysics. The purpose of this paper is to characterize and compare quantitatively a set of recent three‐dimensional models of the elastic structure of the Earth, to assess their similarities and differences, and to analyze their fit to one class of data in order to highlight fruitful directions for future research. The aspherical models considered are the following: M84C (Woodhouse and Dziewonski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(55 citation statements)
references
References 143 publications
1
54
0
Order By: Relevance
“…Here, the qualifter "important" obviously refers to long-wavelength heterogeneity whose omission would otherwise seriously affect the conclusions reached for theoretical parameters (such as viscosity) or the preferred theoretical framework (such as whole-mantle versus layered-mantle) within the context of the internal loading formalism. Whether or not mantle heterogeneity is adequately resolved is a question that is at the heart of ongoing seismic tomographic modeling efforts [e.g., Ritzwoller and Lavely, 1995;Natal and Ricard, 1996]. As discussed in section 1, however, it is clear that the current generation of long-wavelength tomographic models does not unambiguously constrain either transition zone or midmantle heterogeneity [Forte et al, 1994;Forte and Woodward, 1997a,b].…”
Section: Tomography Modelsmentioning
confidence: 99%
“…Here, the qualifter "important" obviously refers to long-wavelength heterogeneity whose omission would otherwise seriously affect the conclusions reached for theoretical parameters (such as viscosity) or the preferred theoretical framework (such as whole-mantle versus layered-mantle) within the context of the internal loading formalism. Whether or not mantle heterogeneity is adequately resolved is a question that is at the heart of ongoing seismic tomographic modeling efforts [e.g., Ritzwoller and Lavely, 1995;Natal and Ricard, 1996]. As discussed in section 1, however, it is clear that the current generation of long-wavelength tomographic models does not unambiguously constrain either transition zone or midmantle heterogeneity [Forte et al, 1994;Forte and Woodward, 1997a,b].…”
Section: Tomography Modelsmentioning
confidence: 99%
“…Trampert and Woodhouse [2000] tested all recent long-wavelength fundamental mode phase velocity models against independent waveform data and found a reassuring agreement between them. In a test against independent splitting functions, Ritzwoller and Lavely [1995] showed that a robust pattern of the Earth's mantle emerged at the lowest degrees, even if different data and different mapping strategies were employed. Although this quantitative comparison is now almost 10 years old, more recent long-wavelength models correlate highly with the models in the Ritzwoller and Lavely study.…”
Section: Long-wavelength Modelsmentioning
confidence: 99%
“…Among the success stories of global tomography are the delineation of long-wavelength variations in elastic properties in Earth's mantle, which started in the early 1980s, and the detailed delineation, over the last decade or so, of trajectories of mantle convection [see reviews by, e.g., Dziewonski and Woodhouse, 1987;Woodhouse and Dziewonski, 1989;Masters, 1989;Romanowicz, 1991;Montagner, 1994;Masters and Shearer, 1995;Ritzwoller and Lavely, 1995;Dziewonski, 1996;Masters et al, 2000;Kárason and van der Hilst, 2000;Fukao et al, 2001;Romanowicz, 2003]. It is encouraging to see that increasingly consistent information on the spatial patterns of wave speed variations is emerging from tomographic studies that use different data and/or techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The precise determination of the frequency splitting of seismic modes below 1 mHz is a way to improve 1D density models without any trade-off with elastic parameters, as they are directly linked to the 1D-density profile [Widmer-Schnidrig, 2003]. The splitting of the gravest modes also possesses high sensitivity to the 3D-density structure in the Earth's mantle and core, so their observation can constrain the Earth's lateral density structure [Ritzwoller and Lavely, 1995]. The recent Sumatra-Andaman earthquake on 2004 December 26 is a rare opportunity to improve Earth's models, as this huge event has strongly excited the low-frequency seismic modes both on SG and seismic records.…”
Section: Introductionmentioning
confidence: 99%